Financial Literacy and Retirement Planning : The Russian Case - Klapper, Leora; Panos, Georgios A. (2012)
The authors examine the association of financial literacy with retirement planning in Russia, a country with a relatively old and rapidly aging population, large regional disparities, and a rapidly emerging financial market. They find that only 36.3 percent of respondents in the sample understand interest compounding and only half can answer a simple question about inflation. In a country with widespread public pension provisions, they find that financial literacy is significantly and positively related to retirement planning involving private pension funds and schemes. Thus, along with encouraging the availability of private retirement plans, efforts to improve financial literacy could be pivotal to the expansion of the use of such schemes.